Women’s perception about the discovery of breast cancer amid the covid-19 pandemic - Simone Meira Carvalho; Camilla de Abrahão Andrade; Mariana Barbosa Leite Sérgio Ferreira; Karine Soriana Silva de Souza; Fabiane Rossi dos Santos Grincenkov (PLoS ONE, 2023)
Background Breast cancer is considered a health problem at a worldwide level. In Brazil, the South and Southeast regions have the highest mortality rates. Understanding how they dealt with the diagnostic of a stigmatized disease amid the COVID-19 pandemic and its potential repercussions, may enable healthcare professionals to of life. Thus, this study is aimed at understanding the perception of women about the discovery of breast cancer and the impact of the disease on their lives. Methods A qualitative study, with the participation of forty women with breast cancer, under chemotherapy treatment. It was performed in a hospital specialized in oncology, in Juiz de Fora, Brazil, in 2020 and 2021. Data collection was carried out with semi-structured interviews, which were analyzed with Bardin Content Analysis. Results Based on the central theme "Discovery of the disease", these categories were developed: "Discovery" and "Impact of the disease". A large part of women noticed a change in the breast, even before routine checks. Upon the impact of cancer diagnosis, negative feelings arise, then going through a process of acceptance and coping. Some barriers were faced due to the COVID-19 pandemic, which caused delays in the diagnostic and impact caused by social isolation. Family, friends, and healthcare professionals integrated an important supporting network in order to help coping with the disease. Conclusion The consequences of a breast cancer diagnosis can be devastating. It is necessary that healthcare professionals know and embrace the feelings, beliefs, and values as a part of the aspects related to health. Valuing the supporting network of women suffering from the disease may favor the process of accepting and coping with the neoplasm. The COVID-19 pandemic is highlighted as an obstacle to be overcome specially when it comes to diagnostic assistance and availability of a support network. In that sense, it is worth mentioning the importance of a healthcare team able to offer full assistance, with quality. The need of further studies to determine the impact of the pandemic in the long run.